Meta-Analysis: The Effect of Electronic Learning Media on Students' 21st Century Skills in The Industrial Revolution Era 4.0 - Fleony Dea Amanda; Yelfi Rahmi; Asrizal; Akmam (Postgraduate, University of Mataram, 2023)
The industrial revolution era, which is characterized by the entry of technology into all spheres of life, including education, has an impact on 21st century learning. Critical thinking, communication, collaboration, creativity, and innovation are the focus of this 21st century learning. This kind of study is a meta-analysis study, which gathers, examines, and compares data from several previously finished investigations. Â The research sample was made up of 24 source papers that met the requirements for the problem formulation. The data analysis technique applied in this study reduces the impact of each publication. It has been found that electronic learning media have the following effects on 21st century skills in the industrial revolution era: First, depending on the kind of media, AR is the most successful in affecting 21st century abilities. Second, according to the classification of 21st century skills, technology-based learning materials have an impact on critical thinking, creativity, and communication abilities. In the sense that technology-based learning media has a significant effect size for improving students' 21st century skills in the era of the industrial revolution 4.0